(untitled) (International Journal of Applied Research in Management and Economics, 2020)
The supplier selection process has become an important area of research and professional activity, and it is fundamental to understand the types and trends of research in this field. The appropriate supplier selection decision is a fundamental strategic process and plays an important role in supply chain management. In the last decade, academic research on sustainability has evolved rapidly in the supply chain literature. However, there has been scant opportunity for the research community to complete a global assessment of sustainable supplier selection activities to date. This paper seeks to address this need by exploring sustainability in supply chain management, developing a sustainable supplier selection framework with a tool for its operationalization to help managers evaluate supplier selection decisions. Our proposed model is based on the TOPSIS concept as a multiple criteria decision-making (MCDM) model and is validated through a case study. This research work follows the best-in-class approach to comply with all applicable environmental regulations and laws in the supplier selection process.